ANALISIS PERMASALAHAN YANG DIHADAPI WALI KELAS DALAM PEMBELAJARAN ANAK BERKEBUTUHAN KHUSUS (ABK) DI SD NEGERI 169 PEKANBARU - Putri Amelia; Syahrilfuddin Syahrilfuddin; Otang Kurniaman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: The understanding by homeroom teacher in the learning of children with special needs in inclusive schools is an obstacle in its implementation. This study aims to determine and describe the problems faced by homeroom teachers in inclusive schools. The location of this research is in elementary school of 169 Pekanbaru and this carried out in the even semester of 2020-2021. The type of research used in this research is qualitative research. This research uses a descriptive method. The subjects in this study were two homeroom teachers who taught children with special needs in lower grades. Data collection was carried out using observation, interviews, and documentation. The results showed that hoomeroom problem in learning children with special needs is about understanding inclusive, understanding children with special needs, proaktif and friendly attitude, learning design, value standards, and the implementation of learning class so it does not working properly.Key Words: Problems of homeroom teachers, inclusive, children with special needs